A review of novel optical imaging strategies of the stroke pathology and stem cell therapy in stroke - Aswendt, Markus; Adamczak, Joanna; Tennstaedt, Annette (Frontiers in Cellular Neuroscience, 2014)
Transplanted stem cells can induce and enhance functional recovery in experimental stroke. Invasive analysis has been extensively used to provide detailed cellular and molecular characterization of the stroke pathology and engrafted stem cells. But post mortem analysis is not appropriate to reveal the time scale of the dynamic interplay between the cell graft, the ischemic lesion and the endogenous repair mechanisms. This review describes non-invasive imaging techniques which have been developed to provide complementary in vivo information. Recent advances were made in analyzing simultaneously different aspects of the cell graft (e.g. number of cells, viability state and cell fate), the ischemic lesion (e.g. blood brain barrier consistency, hypoxic and necrotic areas) and the neuronal and vascular network. We focus on optical methods, which permit simple animal preparation, repetitive experimental conditions, relatively medium-cost instrumentation and are performed under mild anesthesia, thus nearly under physiological conditions. A selection of recent examples of optical intrinsic imaging, fluorescence imaging (FLI) and bioluminescence imaging (BLI) to characterize the stroke pathology and engrafted stem cells are discussed. Special attention is paid to novel optimal reporter genes/probes for genetic labeling and tracking of stem cells and appropriate transgenic animal models. Requirements, advantages and limitations of these imaging platforms are critically discussed and placed into the context of other non-invasive techniques, e.g. magnetic resonance imaging (MRI) and positron emission tomography (PET), which can be joined with optical imaging in multimodal approaches.